Vantagem competitiva que cresce em árvore: um estudo sobre integração vertical na cadeia de papel e celulose do Brasil - Schmidt, Rodrigo de Holanda (2017)
Purpose – The aim of this study was to comprehend the main determinant factors for vertical integration in the pulp and paper sector in Brazil, from a perspective of pulp manufacturers. Design/methodology – The research adopted a qualitative approach, through a multiple case study with three of the main companies in the pulp and paper sector in Brazil. The data collection was done through semi-structured interviews of executives of the selected companies. Findings – The main competitive advantage arises from the vertical integration backward, of the pulp mill towards the forestry. The main factors for this are the exercise of the market power of oligopoly by the pulp companies, assurance of supply of their main input, the wood, asset specificity of site, shortening the distance between the forest and the pulp mill, and mitigation of uncertainty. There is tapered integration of pulp mill and forestry, mainly due the use of advantages of site specificity of forest producers near the mill, the need to mitigate social risks and to develop a mature market for the commercialization of wood in the country. Research limitations – The main limitation of this work is the fact that the pulp sector is a concentrated oligopoly, with few companies, which restricts the diversity and number of respondents. Practical implications – The results can be applied to organizations in the pulp and paper sector, as well as to other capital-intensive industries with high dependence on a particular raw material. Originality– To our knowledge, this is the first study about vertical integration in the pulp and paper sector in Brazil.